Nrf2 activation protects the liver from ischemia/ reperfusion injury in mice - Kudoh, Kazuhiro (2014)
OBJECTIVE: To investigate the role of Nrf2 in the pathogenesis of hepatic ischemia-reperfusion (I/R) injury. SUMMARY BACKGROUND DATA: Hepatic I/R injury is a serious complication that leads to liver failure after liver surgery. NF-E2-related factor 2 (Nrf2) is a transcription factor that plays a critical role in protecting cells against oxidative stress. Therefore, it is suggested that Nrf2 activation protects the liver from I/R injury. METHODS: Wild-type (WT) and Nrf2-deficient mice were treated with 15-deoxy-Δ(12, 14)-prostaglandin J(2) (15d-PGJ(2)), or a vehicle. Subsequently, these mice were subjected to 60 min hepatic 70% ischemia followed by reperfusion. Liver and blood samples were collected to evaluate liver injury and mRNA expressions. RESULTS: After hepatic I/R, Nrf2-deficient livers exhibited enhanced tissue damage, impaired GSTm1, NQO1, and GCLc inductions, disturbed redox state, and aggravated TNF-α mRNA expression in comparison to WT livers. 15d-PGJ2 treatment protected the livers of WT mice from I/R injury via increased expressions of GSTm1, NQO1 and GCLc, maintained redox status, and decreased TNF-α induction. These effects induced by 15d-PGJ2 were not seen in the livers of Nrf2(−/−) mice and were not annulled by PPARγ antagonist in Nrf2(+/+) mice, suggesting that the protective effect of 15d-PGJ2 is mediated by Nrf2-dependent antioxidant response. CONCLUSIONS: Nrf2 plays a critical role in the mechanism of hepatic I/R injury and would be a new therapeutic target for preventing hepatic I/R injury during liver surgery.